Results in the Latin America and Caribbean Region 2020, Volume 15 - World Bank (World Bank, Washington, DC, 2022)
The COVID-19 pandemic completely changed priorities and policy actions in Latin America and the Caribbean over the past year. The health emergency response became the first immediate challenge, focused on saving lives and mitigating the devastating effects of the pandemic as it progressed through the region. The World Bank Group stood side by side with governments, supporting health emergency efforts in 21 countries to contain the virus, its impact on the economy and, most importantly, protect the poor and most vulnerable.